Estudo clássico e quântico da dissociação molecular induzida por laser - Bolorino, Ivan Luiz [UNESP] (2014)
In this work we investigate the dissociation of heteronuclear diatomic molecules subjected to laser pulses. The study was performed using the one-dimensional driven Morse oscillator model. The investigation was carried out by both classical and quantum mechanics. In the classical point of view, the model presents chaotic dynamics associated with the internuclear potential anharmonicity and with the permanent dipole coupling with the laser electrical field. The solutions for the quantum equations of motion were obtained combining the solution on a spatial grid along with an expansion in the oscillator eigenstate basis. We consider the parameters relative to Nitric Oxide (NO) and Iodine Bromide (IBr) molecules and we study the effect of distinct dipole moment in the classical dissociation. Furthermore, we investigate the dependence of the dissociation probability on the temperature, making a comparative study between classical and quantum results. We found some situation where the classical and quantum results exhibit certain agreement in the behavior of the dissociation threshold